Assessment of the Risks of the Major Use Antibiotics in China's Surface Waters Using a Probabilistic Approach. (26th November 2019) - Li, Qi; Cheng, Bo; Liu, Shan; Zhang, Yibo; Zhou, Li; Guo, Jiahua
ABSTRACT: The occurrence of antibiotics in China's surface waters is an emerging concern. Although the ecological risk assessment for a small number of antibiotics is available in some regions, no attempt has been made to assess their risks at a national scale. The present work therefore proposed a probabilistic approach to characterize the ecological risks of 26 major use antibiotics, including sulfonamides, tetracyclines, beta‐lactams, fluoroquinolones, and macrolides, in China's surface waters. Initially we performed exposure and hazard assessment for these substances by synthesizing and interpreting the available occurrence and ecotoxicity data. For 22 antibiotics with sufficient ecotoxicity data, we assessed their risks by constructing joint probability curves (JPCs), from which their expected ecological risk (EER) estimates were less than 1%; for all the 26 antibiotics, in conjunction with the exposure distribution curves (EDCs), an assessment factor (AF) approach was applied and the potential risks were only detected for amoxicillin, ciprofloxacin, and penicillin with risk quotients (RQs) of 1.04, 1.54, and 5.83, respectively. These results indicated that the ecological risks of most major use antibiotics posed to nontarget organisms in China's aquatic environment seem to be low. Nevertheless, there are large uncertainties in the risk characterization processes, likely because of the significant data gaps in the understanding of exposure and hazards of these antibiotics. Integr Environ Assess Manag 2019;00:1–10. © 2019 SETAC KEY POINTS: A probabilistic approach using measured environmental concentrations well represents the exposure to antibiotics in China's surface waters. A lack of ecotoxicity data for 4 antibiotics hinders the derivation of joint probability curves. The potential risks are only detected for amoxicillin, ciprofloxacin, and penicillin, with risk quotients of 1.04, 1.54, and 5.83, respectively. Although the ecological risks for most of the antibiotics seem to be low in China's aquatic environment, high uncertainty exists because of the knowledge gaps in the long‐term effects of antibiotics.